PEMBERDAYAAN MASYARAKAT DESA LEREP KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG MELALUI BADAN USAHA MILIK DESA (BUMDes) GERBANG LENTERA - Sari, Dwi Inda; ., Kushandajani (Journal of Politic and Government Studies, 2020)
The village is expected to have an institution that can empower the community as well as economic enhancement and indigenous village revenue. Thevillage owned enterprises (BUMDes) is a business entity that is wholly or largelyowned by the village through direct inclusion derived from a wealth of villagesseparated to manage assets, service and other businesses to for the welfare of thevillage community. This research aims to explain the form of empowerment of villagecommunity through the business unit of BUMDes and analyze supporting factorsand barriers to community empowerment and how the development of business unitBUMDes run against a village primarily in providing welfare to local communitiesthrough community empowerment. Research methods used are qualitativedescriptive with data collection techniques in the form of interviews anddocumentation. Data obtained later in the analysis using Data interpretationAnalysis, theory, and Data sources.The findings of this research is that community Empowerment LerepVillage District West Ungaran Semarang District through the village-ownedenterprises (BUMDes) Lantern Gate, just go well, it is seen from business units thatrun and Tourism potentials that exist in the pack and managed to become a form ofcommunity empowerment through BUMDes become a tour package. The existenceof cooperation with third parties and trainings to make existing potentials andbusiness units run more developed. The supporting factors are the participation ofactive communities, government support, as well as the potential for adequatenatural resources while for the barriers faced by the absence of special training heldfrom the manager to develop Citizen independence, limited funds to develop thebusiness unit run, and limited human resources in the management of BUMDes.Empowerment made through the business unit that is carried out by BUMDesaffects 2 sectors. Economic sectors have an impact on the increasing communityincome of Lerep Village and the opening of employment, and the social impact thatthere is a promotion of the village Lerep Tourism, the study of appeals conductedby other villages to visit Lerep Tourism Village About the management ofBUMDes and the training provided by other parties to the people of Lerep villageto grow and able to manage the potential.Keywords: community empowerment, village owned enterprises (BUMDes)